IMPLEMENTASI MEDIA JERSEY BERANGKA DALAM MENINGKATKAN HASIL BELAJAR MENGURUTKAN BILANGAN DI MADRASAH IBTIDAIYAH - Nur Nafisatul Fithriyah; Anisatul Karimah; Khusnul Mu’alifah (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2022)
This research was conducted because the majority of student learning outcomes were below the minimum completeness criteria, the mathematics learning carried out was still conventional, namely the delivery of material was still with lectures and students had not been directly involved in problem solving. In general, this research is to improve learning outcomes of sorting numbers through numbered jersey media for second grade students of MI Miftahul Ulum. This research uses classroom action research, in this study there are two cycles consisting of planning, implementation, observation and reflection. Data collection techniques used are observation, tests, and documentation. Observations were made about student activity and teacher activity, the tests used were written tests, and documentation was photos during the research. The results of the classroom action research showed that the numbered jersey media could improve student learning outcomes, in the first cycle the student learning outcomes were 42.85% (6 students who completed) and 57.15% (8 students who completed) while in the second cycle it was 85.72 % (12 students who complete) and 14.28 (2 who have not completed), so that students achieve the minimum criteria for completeness that have been determined, and student activity in the learning process has increased. Using media during teaching and learning activities can increase students' willingness to continue learning, by using media the learning process is not only teacher-centered but also involves students.